Oppressing Intersections: A Critique of Colson Whitehead’s The Underground Railroad and The Intuitionist - R. Gibbson Henry; Dr. R. Princee (Educational Administration: Theory and Practice, 2024)
Intersectionality, a concept proposed by American Civil Rights advocate Kimberlé Crenshaw, holds that the identity of individuals are determined by various factors like race, sex, age, class, gender, disability, sexual orientation, nationality, etc. These categories are framed by power structures for social grouping of humans, which ultimately results in the marginalization of certain groups. This research article utilizes intersectionality, a primarily sociological tool, for literary analysis of the novels of Colson Whitehead. Through his portrayal of Black female protagonists, Cora and Lila Mae, in The Underground Railroad and The Intuitionist respectively, the triple oppression faced by African American women is elucidated. The behavioural attitudes of Cora and Lila Mae are conditioned by external social factors that are vital elements of intersectionality. Even though the characters resist the oppression, they couldn’t execute it to the fullest as they are unconscious victims of intersectionality. The interconnectedness of identity by race, class and gender shape the trajectory of both Black men and women. This study presents the resistance exercised by the protagonists, who in spite of being multiply subjugated show admirable traits to overcome adversities. The paper further analyzes how the novel challenges the remnant notions of womanhood and chastity, which were historically imposed upon white middle class women by early feminist movements. By performing an intersectional analysis instead of adopting a single-axis approach that focuses on either race or gender or class at a time, the paper attempts a faithful representation of the true extent of oppression. The study concludes with the solutions that are discovered in the chosen texts by Whitehead to eradicate the systematic inequalities and promote social justice.